Emotional warmth and cyberbullying perpetration attitudes in college students: Mediation of trait gratitude and empathy - Chen, Liang (PLoS One, 2020)
Based on Social Learning Theory and the General Aggression Model, this study aims to explore the relationship between parental emotional warmth and the cyberbullying perpetration attitudes of college students and the mediating roles of trait gratitude and empathy. Using the stratified cluster random sampling method, 1198 college students (716 boys and 482 girls with an average age of 20.44 years) were tested using the subscale of the Parenting Styles Instrument, the Basic Empathy Scale, the Gratitude Questionnaire-6, and the Cyberbullying Attitude Questionnaire. Results: Emotional warmth, trait gratitude, cognitive empathy, and affective empathy all demonstrated significantly positive relationships with each other (rs from .175 to .403, ps < 0.01) and negative correlations with cyberbullying perpetration attitudes (rs from -.137 to -.306, ps < 0.01). Emotional warmth can exert an impact on cyberbullying perpetration attitudes through three fully mediating paths: the mediating roles of trait gratitude (41.91% of the total effect), cognitive empathy (14.5% of the total effect), and the chain mediating roles of trait gratitude–cognitive empathy (19.5% of the total effect). The results may have important implications for future studies to develop effective interventions for cyberbullying.